Match the equation with the step needed to solve it.

1. 2m - 1 = 3m subtract m
2. 2m = 1 + m subtract 2
3. m - 1 = 2 subtract 1
4. 2 + m = 3 subtract 2m
5. -2 + m = 1 add 2
6. 3 = 1 + m add 1

1 answer

Try the various operations

Only #5 will leave you with an equation for m
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. Match the equation with the step needed to solve it.1. 2m - 1 = 3m subtract m 2. 2m = 1 + m subtract 2 3. m - 1 = 2 subtract 1
    1. answers icon 2 answers
  2. JamalStep 1: Set equation =0 . x2+4x−12=0 Step 2: Write quadratic equation as the product of two factors. (x+6)(x−2)=0 Step
    1. answers icon 2 answers
more similar questions